Penerapan model pembelajaran RADEC untuk meningkatkan pemahaman konsep pada materi sistem pernapasan manusia Siswa Kelas V SD - Jatnika, Widuri Tresnawati; Sunaengsih, Cucun; Sujana, Atep (Academy of Education Journal, 2024)
Conceptual understanding ability is a skill in which students can explain a matter or concept of knowledge with their personal understanding. However, students' conceptual understanding related to science learning, especially on the material of the human respiratory system is still lacking. This study aims to determine how the application of the RADEC learning model in improving concept understanding in human respiratory system material for grade V elementary school students. This research used experimental method with quasi experimental design nonequivalent control groups design. The results showed that the pretest of students' concept understanding ability was highest with a score of 60 with an average score of 33. After the application of the RADEC learning model, the posttest value of students' concept understanding was highest in the very good category with a score of 100 with an average score of 82. The increase in students' understanding of concepts in human respiratory system material after applying the RADEC learning model has increased significantly as evidenced by the n-gain results on students' pretest and posttest scores with a result of 0.72 which is in the high category indicating that there is an increase in understanding of high category concepts after the application of the RADEC learning model of human respiratory system material.